“For a while they felt better”: Negation in A Flag for Sunrise - Brady Harrison (European Journal of American Studies)
In A Flag for Sunrise, American novelist Robert Stoneexplores the metaphysics of empire, attempting to understand what fears, desires, and ontological conditions impel imperialism. Beneath the stories our leaders tell us to justify interventionism, Stone contends, dwell deep - seated, but over - indulged fears that have twisted many into vicious empire - builders and seekers - after - death. Fear eats away at the self: fear of death, fear of the void within, fear of human meaninglessness, fear of groundlessness in a Godless universe impel the agents of empire forward. Charges into the third world arise from these intertwining fears, from the ache within that can only be briefly quieted through acts of brutality, appropriation, conquest. Imperialism, he suggests, grows from a need to fill this void within, or at least to shut one=s eyes to it through ferocious activities and desires.